Gandhi - Rogers, Susan (Zaner-Bloser, Inc.)
This books is a biography of Gandhi who throughout his life time brought freedom to the people of Indian. He set an example for how to live in peace and also show the people of indian that they could change their world without fighting.
Keywords: Juvenile Non-Fiction / Biographies